An oral health literacy intervention for Indigenous adults in a rural setting in Australia - Parker Eleanor J; Misan Gary; Chong Alwin; Mills Helen; Roberts-Thomson Kaye; Horowitz Alice M; Jamieson Lisa M (BMC, 2012)
Abstract Background Indigenous Australians suffer substantially poorer oral health than their non-Indigenous counterparts and new approaches are needed to address these disparities. Previous work in Port Augusta, South Australia, a regional town with a large Indigenous community, revealed associations between low oral health literacy scores and self-reported oral health outcomes. This study aims to determine if implementation of a functional, context-specific oral health literacy intervention improves oral health literacy-related outcomes measured by use of dental services, and assessment of oral health knowledge, oral health self-care and oral health- related self-efficacy. Methods/design This is a randomised controlled trial (RCT) that utilises a delayed intervention design. Participants are Indigenous adults, aged 18 years and older, who plan to reside in Port Augusta or a nearby community for the next two years. The intervention group will receive the intervention from the outset of the study while the control group will be offered the intervention 12 months following their enrolment in the study. The intervention consists of a series of five culturally sensitive, oral health education workshops delivered over a 12 month period by Indigenous project officers. Workshops consist of presentations, hands-on activities, interactive displays, group discussions and role plays. The themes addressed in the workshops are underpinned by oral health literacy concepts, and incorporate oral health-related self-efficacy, oral health-related fatalism, oral health knowledge, access to dental care and rights and entitlements as a patient. Data will be collected through a self-report questionnaire at baseline, at 12 months and at 24 months. The primary outcome measure is oral health literacy. Secondary outcome measures include oral health knowledge, oral health self-care, use of dental services, oral health-related self-efficacy and oral health-related fatalism. Discussion This study uses a functional, context-specific oral health literacy intervention to improve oral health literacy-related outcomes amongst rural-dwelling Indigenous adults. Outcomes of this study will have implications for policy and planning by providing evidence for the effectiveness of such interventions as well as provide a model for working with Indigenous communities.